Impact of ionospheric disturbances on NIC and NACp degradation in ADS-B messages - Takahashi, Toru; Pongpeaw, Anurak; Saito, Susumu; Koga, Tadashi; Supnithi, Pornchai; Budtho, Jirapoom (My University, 2025)
Southern Japan is located in the low geomagnetic latitude region, where amplitude scintillations associated with equatorial plasma bubbles are often observed. The Electronic Navigation Research Institute (ENRI) has installed GNSS scintillation receivers and an all-sky camera on Ishigaki Island to monitor ionospheric disturbances. The GNSS receivers used are Septentrio Pola5S, which are also utilized for the Ground Based Augmentation System (GBAS) at New Ishigaki Airport (24.4 deg. N, 124.2 deg. E), which is the southernmost airport with regular flights in Japan. The all-sky camera can capture ionospheric disturbances, such as plasma bubbles. The ADS-B receiver has also been installed at Ishigaki Island and received its message within almost 150 NM. The ADS-B observation on Ishigaki Island has been operational since 2023. We observed that plasma bubbles and degradations in NIC and NACp values occurred simultaneously on March 16, 2024. We calculated the Ionospheric Pierce Points (IPP) of GPS satellites observed by aircraft showing degraded NIC and NACp values. Plasma bubbles captured by the all-sky camera were projected onto the map. One GPS satellite's IPP from the flight, which sent those degraded values, was located at the edge of a plasma bubble, and the potential impact of the plasma bubble was considered. However, same analyses were conducted on two other satellites flying in the vicinity, and although these two flights were in conditions that were either equivalent to or more susceptible to the effects of the plasma bubble, neither the NIC nor NACp showed any degradation. Therefore, Instead, radio frequency interference (RFI), or equipment failure is likely one of the causes of these degradations.